Remittances, Capital Flows and Financial Development during the Mass Migration Period, 1870‐1913. - Esteves, R; Khoudour-Castéras, D (CEPII, 2009)
This paper addresses the question whether the substantial financial flows received by emigration countries in the four decades running up to World War I contributed to domestic financial development in peripheral Europe. We quantify a sizable and significant relation between remittances and measures of development of the financial sector that is both larger than the contribution of other international capital flows and than the best estimates of the same relation in our days. Given that financial development is regularly included among the conditions for economic growth and catch up of developing nations, this paper adds to our understanding of the multiple impacts of the mass migration phenomenon on the economies of emigration countries.